2012
DOI: 10.4097/kjae.2012.63.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil used as adjuvant in general anesthesia for spinal fusion does not exhibit acute opioid tolerance

Abstract: BackgroundAlthough acute tolerance to opioids, especially to remifentanil, has been demonstrated consistently in animal studies, the results of clinical trials in humans are controversial. The aim of this study was to determine whether intraoperative infusions of remifentanil used as an adjuvant in general anesthesia result in acute tolerance, an event manifested by increased postoperative pain and a higher opioid requirement than usual.MethodsSixty patients who underwent surgery under general anesthesia for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…A prospective, randomized, double-blind study, showed that 3 h infusion of remifentanil of 0.3 μg/kg/min did not increase postoperative pain or opioid consumption in cardiac surgery patients who underwent sufentanil/propofol-based general anesthesia ( Lahtinen et al, 2008 ). Yeom et al (2012) suggested that remifentanil did not appear to cause AOT and OIH in patients undergoing spinal fusion even though there was significant differences in the mean intraoperative infusion rate of remifentanil (0.16 μg/kg/min vs. 0.03 μg/kg/min) for a short period of time (averaging 225 and 216 min, respectively). Schraag et al (1999) found that Remifentanil infusion using specially designed patient-maintained TCI systems, which was controlled according to the patients demand for postoperative pain control by up-and-down method (intervals 0.2 ng/ml) did not show any evidence of rapid development of acute tolerance in patients maintained hypnotic dose of remifentanil in the first six postoperative hours from end of total intravenous anesthesia with remifentanil and propofol.…”
Section: Controversial Results On Development Of Aot and Oih By Remifmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective, randomized, double-blind study, showed that 3 h infusion of remifentanil of 0.3 μg/kg/min did not increase postoperative pain or opioid consumption in cardiac surgery patients who underwent sufentanil/propofol-based general anesthesia ( Lahtinen et al, 2008 ). Yeom et al (2012) suggested that remifentanil did not appear to cause AOT and OIH in patients undergoing spinal fusion even though there was significant differences in the mean intraoperative infusion rate of remifentanil (0.16 μg/kg/min vs. 0.03 μg/kg/min) for a short period of time (averaging 225 and 216 min, respectively). Schraag et al (1999) found that Remifentanil infusion using specially designed patient-maintained TCI systems, which was controlled according to the patients demand for postoperative pain control by up-and-down method (intervals 0.2 ng/ml) did not show any evidence of rapid development of acute tolerance in patients maintained hypnotic dose of remifentanil in the first six postoperative hours from end of total intravenous anesthesia with remifentanil and propofol.…”
Section: Controversial Results On Development Of Aot and Oih By Remifmentioning
confidence: 99%
“…There is controversial results on AOT and OIH induced by remifentanil at the perioperative period, even though many authors suggested that remifentanil could induce them ( Schraag et al, 1999 ; Cortinez et al, 2001 ; Hansen et al, 2005 ; Lahtinen et al, 2008 ; Angst et al, 2009 ; Yeom et al, 2012 ). Angst et al (2009) documented that 3 h infusion of remifentanil of up to 4.0 ng/ml was not associated with the development of significant tolerance to analgesic in placebo-controlled, double-blind study.…”
Section: Controversial Results On Development Of Aot and Oih By Remifmentioning
confidence: 99%
“…All included trials administered volatile anaesthetics to maintain anaesthesia except five that administered propofol [27,30,31,36,39]. Regarding the types of surgery, authors included patients scheduled for gynaecological surgery in eight trials [25-27, 31, 33, 37, 44, 45]; patients undergoing abdominal surgery in six trials [28,35,36,38,41,42]; and finally, we combined the remaining nine trials together into an 'other surgery' group [29,30,32,34,39,40,43,46,47].…”
Section: This Investigation Was Conducted Following the 'Preferredmentioning
confidence: 99%
“…[16][17][18][19]21,22,24 Differences in the cumulative intraoperative opioid dose could at least partially explain the divergent findings. Focusing on studies administering remifentanil indicates that aggravated postoperative pain and/or increased opioid consumption was consistently reported if patients received a cumulative dose greater than 50 µg/kg but could not reliably be detected if patients received a smaller cumulative dose (Fig 2).…”
Section: Increased Postoperative Pain And/or Opioid Consumptionmentioning
confidence: 99%